A randomized, controlled clinical trial comparing remimazolam to propofol when combined with alfentanil for sedation during ERCP procedures - Dong, Shu-An; Guo, Yan; Liu, Sha-Sha; Wu, Li-Li; Wu, Li-Na; Song, Kai; Wang, Jing-Hua; Chen, Hui-Rong; Li, Wei-Zhi; Li, Huan-Xi; Zhang, Li; Yu, Jian-Bo (Journal of clinical anesthesia, 2023)
In many countries, the combination of propofol and opioid is used as the preferred sedative regime during ERCP. However, the most serious risks of propofol sedation are oxygen deficiency and hypotension. Compared to midazolam, remimazolam has a faster onset and offset of hypnotic effect, as well as cardiorespiratory stability, and to achieve widespread acceptance for procedural sedation, remimazolam must replace propofol which is the most commonly used for procedural sedation. The objective of this study was to compare the safety and efficacy profiles of the remimazolam and propofol when combined with alfentanil for sedation during ERCP procedures. A randomized, controlled, single-center trial. The Endoscopic Centre of Tianjin Nankai Hospital, China. 518 patients undergoing elective ERCP under deep sedation. Patients scheduled for ERCP were randomly assigned to be sedated with either a combination of remimazolam-alfentanil or propofol-alfentanil. The primary outcome was the prevalence of hypoxia, which was defined as SpO2 < 90% for >10 s. Other outcomes were the need for airway maneuver, procedure, and sedation-related outcomes and side effects (e.g., nausea, vomiting, and cardiovascular adverse events). A total of 518 patients underwent randomization. Of these, 250 were assigned to the remimazolam group and 255 to the propofol group. During ERCP, 9.6% of patients in the remimazolam group showed hypoxia, while in the propofol group, 15.7% showed hypoxia (p = 0.04). The need for airway maneuvering due to hypoxia was significantly greater in the propofol group (p = 0.04). Furthermore, patients sedated with remimazolam had a lower percentage of hypotension than patients sedated with propofol (p < 0.001). Patients receiving remimazolam sedation expressed higher satisfaction scores and were recommended the same sedation for the next ERCP. The procedure time in the remimazolam group was much longer than in the propofol group due to the complexity of the patient's disease, which resulted in a longer sedation time. During elective ERCP, patients administered with remimazolam showed fewer respiratory depression events under deep sedation with hemodynamic advantages over propofol when administered in combination with alfentanil. •The combination of propofol and an opioid is the preferred sedative regime during ERCP.•The major concerns with propofol sedation include oxygen desaturation and hypotension.•Patients administered with remimazolam showed fewer respiratory depression events and hemodynamic advantages over propofol.•These results may provide more options for ERCP sedation.